2022
DOI: 10.1002/pon.5889
|View full text |Cite
|
Sign up to set email alerts
|

Is the EORTC QLQ‐C30 emotional functioning scale appropriate as an initial screening measure to identify brain tumour patients who may possibly have a mood disorder?

Abstract: Background Screening glioma patients regularly for possible mood disorders may facilitate early identification and referral of patients at risk. This study evaluated if the EORTC QLQ‐C30 Emotional Functioning (EF) scale could be used as an initial screening measure to identify patients possibly having a mood disorder. Methods EORTC QLQ‐C30 EF and Hospital Anxiety and Depression Scale (HADS) scores were collected as part of a study assessing the impact of timing of patient‐reported outcome assessments on actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In some studies, clinical disease features and emotional characteristics were combined as unique biomarkers that are involved in the clinical diagnostic process. They have also been used to assess patients’ performance during treatment and to aid in implementing psychological intervention therapies [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, clinical disease features and emotional characteristics were combined as unique biomarkers that are involved in the clinical diagnostic process. They have also been used to assess patients’ performance during treatment and to aid in implementing psychological intervention therapies [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Quirien (2022) suggested that the regular use of the European Organization for Research and Treatment of Cancer Core Quality of Life questionnaire (EORTC QLQ-C30) emotional function (EF) scale for screening anxiety and depression symptoms in glioma patients contributes to the early identification of emotional disorders. This practice serves as a foundation for referrals and treatment decisions [ 26 ]. Overall, these studies indicate that psychological care and interventions can enhance patients’ mental well-being within a clinical practice setting.…”
Section: Resultsmentioning
confidence: 99%